(untitled) (GYMNASIUM, 2022)
The aim of this literature study is to provide an overview of research related to the process of teaching - learning online physical education, conducted during the pandemic, from the perspective of responding students. A systematic research of data from the inquiry was performed in six electronic databases, using keywords. The study provides an overview of the effects and difficulties identified following the online physical education classes at the time of the pandemic. The conclusion that emerges from this review indicates that by using combined applications and learning methods in online physical education lessons, the teaching process efficiency level increases, having a positive impact on students’ motivation. By the same time, it also improves the achievement of theoretical knowledge. Several difficulties are identified in the online physical education learning process, especially related to the connection to the internet network or its improper functioning.